Foetal and neonatal outcomes in an era of active management of intrahepatic cholestasis of pregnancy - Bhardwaj, Bikram; Kumar, Vaibhaw; Mounica, Damalapati; Dhillon, G. S.; Kumar H., Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Intrahepatic cholestasis of pregnancy is one kind of hepatic disorder which is unique to pregnancy. It is associated with many adverse pregnancy outcomes if not intervened at the right time. It requires adequate clinical and biochemical correlation during management. Methods: A prospective observational study was conducted in a tertiary care hospital among 1397 patients who underwent delivery during the study period from 01 July 2021 to 30 Jun 2022. Among the study population, those suspected to be having IHCP were subjected to laboratory tests and confirmed cases were further analysed for incidence and pregnancy outcomes in form of several maternal and fetal factors by appropriate statistical test using IBM SPSS version 20.0 Results: During the study period a total of 1397 patients underwent delivery out of which 174 showed clinical signs suggestive of IHCP. On subjecting these 174 suspected cases to further testing 53 patients were diagnosed with IHCP. The incidence of IHCP was 3.7% of which 28.30% (16/53) were primigravida. There were 22.64% (12/53) IVF pregnancies, 11.3% (6/53) were twin pregnancies. Total 28.30% cases (15/53) of IHCP presented with preterm labour. Of the total, there was 7.5% (4 /53) with meconium-stained liquor. Total 54.71% (29/53) cases underwent normal vaginal delivery, one forceps and one VBAC delivery, 45.28% (24/53) cases were underwent LSCS delivery and of this 70.8% (17/24) were emergency caesarean and 29.2% (7/24) were elective caesarean deliveries, 75% (18/24) were primary caesarean delivery. There were 25.4% (15/59) NICU admissions among new born of cases and 28.8% (17/59) were low birth weight babies. 25.4% (15/59) of neonates were seen to have APGAR score of less than 7 at 5 minute There was no stillbirth noted in diagnosed case of IHCP. Conclusions: IHCP causes significant maternal and neonatal morbidity and is major contributor of preterm delivery, caesarean delivery, meconium-stained liquor and NICU admission.